Improving Yield Conversion with Triple Conversion Reactor for Styrene Production from Ethylbenzene - Hutajulu, Febi Tia Maria; Vito, Ahista Aushafa; Fakhira, Fara; Izzati, Dzikrina Sekar (UPT Laboratorium Terpadu, Universitas Diponegoro, 2025)
Styrene is a critical component in various polymer-based materials, with increasing global demand. Its production primarily involves the catalytic dehydrogenation of ethylbenzene, a process requiring high temperatures and facing challenges like by-product formation. This research aims to enhance the yield conversion of styrene using a triple conversion reactor system. The methodology employs Aspen HYSYS simulation, with thermodynamic considerations guiding the reactor designs and operating conditions. Results indicate that implementing three reactors increased the conversion rate from 96% to 99.9% and achieved 99.5% styrene purity. The study concludes that process optimization significantly improves the efficiency and scalability of industrial styrene production. Copyright © 2025 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).